The Role of Perfusionists during the COVID-19 Pandemic and Clinical Laboratory Technologists: Comparison of Training Systems in Japan and the United States - Dong-Ok Aum; Dae Jin Kim; Dae Eun Kim; Myong Soo Kim; Bon-Kyeong Koo (Korean Journal of Clinical Laboratory Science, 2022)
In 2022, Korea reported a total of 224 perfusionists, employing nurses or clinical laboratory technologists (also known as medical technologists) to provide hospital self-education or reliable education. In 2021, the total number of perfusionists in Japan was 2,100, mainly supported by clinical engineering technologists. During the same period, the number of perfusionists reported in the United States was 4,212, who had received training in the master’s program, post-bachelor certificate program, and bachelor’s program. Most personnel in the USA were graduates of healthcare sciences or life sciences. Perfusionists must be knowledgeable in heart anatomy, physiology, pharmacology, pathology, hemodynamics, laboratory analysis, and quality assurance, as well as techniques to operate the cardiopulmonary bypass machine (heart-lung bypass machine). These are jobs similarly handled by clinical laboratory technologists. The importance of perfusionists became more prominent during two major crises: the MERS-CoV and COVID-19 pandemic. Currently, perfusionists play a significant role in the rapidly expanding field of extracorporeal membrane oxygenation (ECMO) and extracorporeal circulation during cardiac surgery. Results : of the current study indicate that hospitals offering cardiac surgery and infectious disease hospitalization need to be institutionalized to secure a certain number of qualified perfusionists. In the future, we look forward to establishing a perfusion technology association under the Korean Society for Clinical Laboratory Physiology to provide academic exchanges.